2021
DOI: 10.1186/s13071-021-04651-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of binary protein–protein interactions between tick-borne flaviviruses and Ixodes ricinus

Abstract: Background Louping ill virus (LIV) and tick-borne encephalitis virus (TBEV) are tick-borne flaviviruses that are both transmitted by the major European tick, Ixodes ricinus. Despite the importance of I. ricinus as an arthropod vector, its capacity to acquire and subsequently transmit viruses, known as vector competence, is poorly understood. At the molecular scale, vector competence is governed in part by binary interactions established between viral and cellular proteins within infected tick c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 123 publications
0
10
0
3
Order By: Relevance
“…ticks in the Mediterranean and Balkan regions. Several studies on TBEV have used (directly or indirectly) the existing I. ricinus cell lines derived from UK and German ticks [7,[55][56][57][58][59][60]; the new I. ricinus lines derived from Spanish ticks will add a new dimension to research on TBEV-vector interactions. D. reticulatus is also suspected to be a natural vector of TBEV [57,61], but in vitro investigations have been hampered by the lack of any cell lines from this species.…”
Section: Discussionmentioning
confidence: 99%
“…ticks in the Mediterranean and Balkan regions. Several studies on TBEV have used (directly or indirectly) the existing I. ricinus cell lines derived from UK and German ticks [7,[55][56][57][58][59][60]; the new I. ricinus lines derived from Spanish ticks will add a new dimension to research on TBEV-vector interactions. D. reticulatus is also suspected to be a natural vector of TBEV [57,61], but in vitro investigations have been hampered by the lack of any cell lines from this species.…”
Section: Discussionmentioning
confidence: 99%
“…In short, 500 ng of pDONR207 vector was mixed with 2 µL of PCR product and 2 µL of BP Clonase™ in a final volume of 10 µL. The pDONR207 construct was amplified after transformation of E. coli DH5α (NEB) and extracted from bacteria using a NucleoSpin Plasmid kit (Macherey Nagel, Duren, Germany) following the manufacturer’s instructions [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…While progress has been made [ 23 , 24 ], genome annotations for tick species are still incomplete making MS-based methods of host factor discovery difficult. However, Lemasson et al [ 25 ] recently reported a yeast two-hybrid (Y2H)-based screen to identify protein–protein interactions of TBEV and louping ill virus (LIV) proteins in tick cells. Here, all TBEV and LIV proteins were screened against a cDNA library generated from Ixodes ricinus -derived cell lines.…”
Section: Low-biased Approaches To Identify Flavivirus Host Factorsmentioning
confidence: 99%